Pendaftaran Tanah Sistematis Lengkap Berbasis Partisipasi Masyarakat (PTSL+PM) di Kabupaten Ngawi - Damar Jati Nurcahyo; Eko Budi Wahyono; Dian Aries Mujiburrohman (Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: The limited human resources that has bbeen a problem in the Ministry of Agrarian Affairs and Spatial Planning/ National Land Agency was resolved by involving the community through the mechanism of Community-Based Complete Systematic Land Registration (PTSL+PM). a PTSL+PM program had been carried out at the Land Office of Ngawi Regency before the technical guidelines were issued, so this raised a question on whether the implementation was in accordance with the regulation in the technical guidelines. The objectives of this study are to (1) Find out the information about the implementation and comparing the activity PTSL+PM in Ngawi Regency to PTSL+PM technical guidelines; (2) Evaluate PTSL+PM in Ngawi Regency. To achieve those objectives, a qualitative research method with a descriptive approach was used. This method described and reviewed each PTSL+PM implementation process in Ngawi Regency so that it could be used to evaluated PTSL+PM technical guidelines to be more effective to be implemented in all regions in Indonesa. The result of this study shows that there are several elements of PTSL+PM implementation in Ngawi Regency that are not in accordance with the technical guidelines, including work maps, measurenments by land data collectors, and criteria and mechanism for forming land data collectors. Ngawi Land Office implemented the PTSL+PM program with the established community participation and is administratively going to follow the technical guidelines of PTSL+PM. Keywords: Land Registration, Community Participation, Technical Guidelines, Work Map Intisari: Keterbatasan sumber daya manusia yang selama ini menjadi kendala di Kementerian ATR/BPN diselesaikan dengan pelibatan masyarakat melalui mekanisme Pendaftaran Tanah Sistematis Lengkap Berbasis Partisipasi Masyarakat (PTSL+PM). Pelaksanaan program PTSL+PM di Kantor Pertanahan Kabupaten Ngawi telah dilaksanakan sebelum Juknis PTSL+PM terbit sehingga menimbulkan permasalahan apakah pelaksanaannya telah sesuai dengan ketentuan dalam Juknis PTSl+PM. Tujuan penelitian ini adalah untuk (1) Mendeskripsikan pelaksanaan dan membandingkan kegiatan PTSL+PM di Kabupaten Ngawi dengan Juknis PTSL+PM; (2) Mengevaluasi PTSL+PM di Kabupaten Ngawi. Untuk mencapai tujuan tersebut, digunakan metode penelitian kualitatif dengan pendekatan deskriptif guna menggambarkan dan mengkaji setiap proses pelaksanaan PTSL+PM di Kabupaten Ngawi sehingga dapat digunakan untuk mengevaluasi Juknis PTSL+PM agar lebih efektif dijalankan di seluruh daerah di Indonesia. Hasil dari penelitian menunjukkan adanya beberapa unsur pelaksanaan PTSL+PM di Kabupaten Ngawi yang tidak sesuai dengan Juknis meliputi peta kerja, pengukuran oleh Puldatan, kriteria dan mekanisme pembentukan Puldatan. Kantor Pertanahan Kabupaten Ngawi melaksanakan program PTSL+PM dengan partisipasi masyarakat yang sudah terbentuk dan secara adminsitrasi akan mengikuti ketentuan Juknis PTSL+PM.